Design and Analysis of Discrete Adjustable Radius Pulley Continuously Variable Transmission - Yuegang Chu; Yun Peng; Hao Zi; Kunpeng Zhao; Aiping Song (Jixie chuandong)
A new type of Continuously Variable Transmission （CVT） with surface-contact friction transmission structure is presented， which is a discrete adjustable radius CVT. The relationship between the size parameters of the discrete adjustable radius pulley transmission structure and the transmission ratio is analyzed. The calculation formula of the critical friction force of the discrete adjustable radius pulley transmission is derived. It is verified that the discrete adjustable radius pulley has large torque transmission capability in theory. In addition， the rotational speed fluctuation analysis based on ADAMS is carried out， and the experimental device of the discrete adjustable radius CVT is built and tested. The results show that the speed fluctuation meets the transmission requirements of most equipments. The new discrete adjustable radius CVT has great development value， which has the characteristics of compact structure and reasonable design.